Linear Progamming Models for Water Pollution Control - Loucks, Daniel P.; Revelle, Charles S.; Lynn, Walter R. (Management Science, 1967)
Two linear programming models are presented for determining the amount of wastewater treatment required to achieve at minimum cost any particular set of stream dissolved oxygen standards within a river basin. Derived from the generalized Streeter-Phelps differential equations used to describe the rates of dissolved oxygen depletion and recovery of streams, these models are adaptable to any river basin configuration. They can be used not only in determining system costs for various quality standards but also for measuring the cost sensitivity to changes in the design stream and wastewater flows and treatment facility location. An example illustrates the use of these models.